Hoover's handbook of world business - Hoover, Gary. (Austin, TX : Reference Press, 1991)
A comprehensive guide to international business covers more than 160 major non-U.S. companies and profiles the sixty most important nations for conducting business
Published by: Hoover's Business Press, 1997-
Includes bibliographical references and index.
Donation from the Asia Foundation/ Savar Campus
Keywords: Corporations -- Directories; Business enterprises. -- Directories